Study of the Electrochemical Behavior of Histamine Using a Nafion (R)-Copper(II) Hexacyanoferrate Film-Modified Electrode. - Castro, Suely S. L. (2010)
A study on the electrochemical behavior of histamine species in aqueous medium is described. A glassy carbon electrode chemically modified with copper(II) hexacyanoferrate (CuHCFe) film and covered with Nafion (R) film was employed. The interaction between the analyte and the CuHCFe film can be demonstrated by a decrease in both the cathodic and anodic peak currents at 0.68V (vs. Ag/AgCl), attributed to the film and the appearance of new peak current at 0.47V. Cyclic voltammetric parameters obtained for histamine indicate the formation of stable complex between histamine adsorbed at the electrode surface. The dependence of peak currents on the concentration of the analyte is not linear in the employed work range, indicating the presence of a coupled chemical reaction in the electrodic process.